Dependence of Lyubeznik numbers of cones of projective schemes on projective embeddings - Reichelt, Thomas; Saito, Morihiko; Walther, Hans Ulrich (Selecta mathematica, 2021)
We construct complex projective schemes with Lyubeznik numbers of their cones depending on the choices of projective embeddings. This answers a question of G. Lyubeznik in the characteristic 0 case. It contrasts with a theorem of W. Zhang in the positive characteristic case where the Frobenius endomorphism is used. Reducibility of schemes is essential in our argument. B. Wang recently constructed examples of irreducible projective schemes (which are not normal) from our examples of reducible ones. So the question is still open in the normal singular case.
Gesehen am 09.02.2021